2013
DOI: 10.1371/journal.pone.0068707
|View full text |Cite
|
Sign up to set email alerts
|

Milk Fat Content and DGAT1 Genotype Determine Lipid Composition of the Milk Fat Globule Membrane

Abstract: During secretion of milk fat globules, triacylglycerol (TAG) droplets are enveloped by a phospholipid (PL) trilayer. Globule size has been found to be related to polar lipid composition and fat content, and milk fat content and fatty acid composition have been associated with the diacylglycerol acyltransferase 1 (DGAT1) K232A polymorphism; however, the association between the DGAT1 polymorphism and fat globule size and polar lipid composition has not been studied. The ratio between polar and neutral lipids as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 36 publications
1
31
0
2
Order By: Relevance
“…Recently, studies by Argov-Argaman et al (2013 and, Logan et al (2014) and Cohen et al (2015) have suggested that the phospholipid (PL) to triacylglycerol (TAG) ratio in cytoplasm, linked to diacylglycerol acyltransferase 1 activity, influences MFG diameter. In the PL, phosphatidylethanolamine, when located in the membrane, would play a major role in the process of intracellular fusion of CLD and thereby in MFG diameter (Keenan and Huang, 1972;Mesilati-Stahy et al, 2011;Argov-Argaman et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies by Argov-Argaman et al (2013 and, Logan et al (2014) and Cohen et al (2015) have suggested that the phospholipid (PL) to triacylglycerol (TAG) ratio in cytoplasm, linked to diacylglycerol acyltransferase 1 activity, influences MFG diameter. In the PL, phosphatidylethanolamine, when located in the membrane, would play a major role in the process of intracellular fusion of CLD and thereby in MFG diameter (Keenan and Huang, 1972;Mesilati-Stahy et al, 2011;Argov-Argaman et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the PL, phosphatidylethanolamine, when located in the membrane, would play a major role in the process of intracellular fusion of CLD and thereby in MFG diameter (Keenan and Huang, 1972;Mesilati-Stahy et al, 2011;Argov-Argaman et al, 2013). Thus, when PL : TAG ratio is high, de novo FA content and synthesis are low.…”
Section: Discussionmentioning
confidence: 99%
“…A potential contributor to these negative effects in intestinal cells could also be the type and concentration of phospholipids with surfactant activity that are bound to allergens (e.g., α-la). The phenotype and genotype influence of both the phospholipid and fat content in the milk products (Argov-Argaman, Mida, Cohen, Visker, & Hettinga, 2013;Mesilati-Stahy & Argov-Argaman, 2014) could also explain in part the differences in the cytotoxic effects.…”
Section: Polarised Mitochondria and Disruption Of Mitochondrial Membrmentioning
confidence: 99%
“…To prevent cow's milk protein allergies (CMPA), researchers have attempted to modify the milk protein structure (Bu, Luo, Chen, Liu, & Zhu, 2013;Chandrapala, Zisu, Kentish, & Ashokkumar, 2012;Wróblewska, Jędrychowski, Hajjós, & Szabó, 2008;Wróblewska et al, 2004). The introduction of vegetal milk or other mammalian milk products has also been considered.…”
Section: Introductionmentioning
confidence: 99%
“…Milk polar lipid composition and concentration are closely associated with lactation stage (Bitman and Wood, 1990), genetic predisposition (Argov-Argaman et al, 2013), plasma insulin concentration (Argov-Argaman et al, 2012) and diet (Lopez et al, 2008). In general, milk polar lipid composition and concentration are altered when systemic or local -within the mammary gland -changes in lipid metabolism are induced.…”
Section: Introductionmentioning
confidence: 99%